Role of magnetic resonance cholangiopancreatography in conjunction with 3D assessment in patients of different billiary obstruction causes - Rahman, Suheel U.; Dar, Rassieq A.; Wani, Basit A.; Dar, Sajad A. (International Surgery Journal, 2022)
Background: Conventional 2d MRCP has pitfalls which may stimulate or mask various pathologic conditions of extrahepatic ducts or pancreatic duct, to overcome this a number of new modern techniques are being used. Methods: Observational study carried out in Government Medical College Srinagar including a total of 50 patients. Results: Gallstone disease was the most common etiology responsible for biliary obstruction. Both Malignant and Benign strictures, IHBR dilatation and pancreatic duct dilatation were better appreciated by 3D MRCP than 2D MRCP. Conclusions: In patients with biliary obstruction, MRCP aims at finding the pathology. It also helps in planning of surgical or interventional management and serves to guide these procedures with 3D MRCP definitely having advantages.